A review study on spiritual intelligence, adolescence and spiritual intelligence, factors that may contribute to individual differences in spiritual intelligence and the related theories - Hosseini, Maryam; Elias, Habibah; Krauss, Steven Eric; Hassan, Siti Aishah (Canadian Center of Science and Education, 2010)
This paper reviewed the articles about adolescence, its relation to spiritual intelligence and the related theories. The adolescence period is the best time to develop positive emotions and training skills, because adolescents are seeking to find their identity and their future personality at this period. Spiritual intelligence has a significant influence on the quality of life and it goes without saying that adolescence is a sensitive period which requires specific training to make a brighter future and be exposed to the difficulties. Spirituality can be viewed as a form of intelligence because it predicts functioning and adaptation and offers capabilities that enable people to solve problems and attain goals. Conceiving spirituality as a sort of intelligence extends the psychologist’s conception of spirituality and allows its association with the rational cognitive processes like goal achievement and problem solving. Emotional intelligence allows us to judge in which situation we are involved and then to behave appropriately within it. Spiritual intelligence allows us to ask if we want to be in this particular situation in the first place.